Implementation of Canva-Based Animated Video Learning Media in the Aswaja Subject for Grade VII at Darul A'mal Plus Middle School, Metro City, Lampung - Linda Nanda Yanti; Ikhwan Aziz Q; M. Zainal Arifin (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This research is motivated by the limitations of media innovation in Aswaja learning, which is still dominated by conventional methods, resulting in low student engagement and understanding of abstract material. This study aims to analyze the implementation of Canva-based animated video learning media in Aswaja learning for grade VII at SMP Plus Darul A'mal, Metro City, and to identify supporting and inhibiting factors. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions with triangulation validity tests. The results show that the integration of Canva-based animated videos in the planning, implementation, and evaluation stages of learning can increase students' motivation, active participation, and conceptual understanding in a more contextual manner. The novelty of this research lies in strengthening the integration of creative digital media in Islamic Religious Education learning as a pedagogical strategy that is adaptive to the characteristics of the digital generation. This study concludes that the use of Canva-based animated video media is effective in supporting more interactive and meaningful Aswaja learning. The implications emphasize the importance of improving digital literacy and teacher pedagogical competence in the development of innovative media.